The word of Bob : an AI Minecraft villager - Nichols, Peter Clifford, 1964- ([Coffs Harbour, N.S.W.] : Peter Clifford Nichols, 2018)
If you were paying to live inside a computer simulation that was guaranteed to feel real, the simulation would not let you read this book. Unless of course....Bob is no ordinary Minecraft villager. Programmed with a Google AI algorithm, he is getting smarter but still cannot be convinced he is inside a game. When he learns the truth he starts on a journey that only 'friendly AI' can travel. This is a children`s book for adults. How far can you follow Bob as his life gradually becomes more complex and his growing understanding of 'reality' makes him question his place in the universe?
Mode of access : Available online.
Keywords: Science fiction; Electronic books; Science fiction